The Transformation of Indonesian Language Literacy Through Banten Local Wisdom with Artificial Intelligence (AI): A Case Study of University Students and High School Students in Banten - Lia Andriani Harahap; Asep Muhyidin; Siti Rodhia (Didaktika: Jurnal Kependidikan, 2025)
The rapid advancement of digital technology, particularly Artificial Intelligence (AI), has influenced the development of literacy and cultural education in Indonesia. This study aims to explore how Indonesian language literacy can be transformed through the integration of Banten’s local wisdom using AI-based approaches. The research adopts a qualitative descriptive method, involving high school and university students in Banten as participants. Data were collected through observations, interviews, and document analysis, and analyzed using the Miles and Huberman model through data reduction, display, and conclusion drawing. The findings show that AI applications—such as natural language processing tools, chatbots, and machine learning systems—can serve as effective media for developing contextual and engaging literacy learning. AI supports students in exploring Banten’s cultural elements, such as debus, pantun, and folktales, while enhancing their creativity, comprehension, and critical awareness. However, the study also reveals limitations of AI, particularly its lack of sensitivity to cultural nuances and the risk of overdependence, which may hinder students’ critical thinking. The study concludes that the transformation of Indonesian language literacy through AI is most effective when balanced with teacher guidance and cultural reflection, ensuring that technology reinforces rather than replaces local wisdom and national identity.